Nuclear magnetic resonance‐ and mass spectrometry‐based metabolomics to study maleic acid toxicity from repeated dose exposure in rats†. Issue 12 (10th July 2017) - Wu, Charlene; Chen, Chi‐Hung; Chen, Hsin‐Chang; Liang, Hao‐Jan; Chen, Shu‐Ting; Lin, Wan‐Yu; Wu, Kuen‐Yuh; Chiang, Su‐Yin; Lin, Ching‐Yu
Abstract: Maleic acid (MA), a chemical intermediate used in many consumer and industrial products, was intentionally adulterated in a variety of starch‐based foods and instigated food safety incidents in Asia. We aim to elucidate possible mechanisms of MA toxicity after repeated exposure by (1) determining the changes of metabolic profile using 1 H nuclear magnetic resonance spectroscopy and multivariate analysis, and (2) investigating the occurrence of oxidative stress using liquid chromatography tandem mass spectrometry by using Sprague–Dawley rat urine samples. Adult male rats were subjected to a 28 day subchronic study (0, 6, 20 and 60 mg kg −1 ) via oral gavage. Urine was collected twice a day on days 0, 7, 14, 21 and 28; organs underwent histopathological examination. Changes in body weight and relative kidney weights in medium‐ and high‐dose groups were significantly different compared to controls. Morphological alterations were evident in the kidneys and liver. Metabolomic results demonstrated that MA exposure increases the urinary concentrations of 8‐hydroxy‐2′‐deoxyguanosine, 8‐nitroguanine and 8‐iso‐prostaglandin F2α ; levels of acetoacetate, hippurate, alanine and acetate demonstrated time‐ and dose‐dependent variations in the treatment groups. Findings suggest that MA consumption escalates oxidative damage, membrane lipid destruction and disrupt energy metabolism. These aforementioned changes in biomarkers and endogenous metabolites elucidate and assist in characterizing the possible mechanisms by which MA induces nephro‐ and hepatotoxicity. Abstract : We aimed to elucidate possible mechanisms of maleic acid toxicity by (1) determining the changes of metabolic profile, and (2) investigating the occurrence of oxidative stress. In rats that underwent a 28 day toxicity study via oral gavage, statistical significant body and organ weight changes were observed in the treatment groups, urinary concentrations of 8‐hydroxy‐2′‐deoxyguanosine, 8‐nitroguanine and 8‐iso‐prostaglandin F2α and levels of several endogenous metabolites, with time‐ and dose‐dependent variations. Findings elucidate the possible mechanisms by which nephro‐ and hepatotoxicity occur.